Media Framing of the Israeli Arabic - Speaking Social Media Pages Directed to the Palestinian Audience - Ihab Ahmed Awais; Sujoud S. Awais; Abeer Z. Alhossary (UKM Press\r\nJurnal Komunikasi: Malaysian Journal of, 2024)
Indexed by WOS/SCOPUS/ERA